Temporal trends and black–white disparity in mortality among hospitalized persons living with HIV in the United States. Issue 9 (March 2019) - Salihu, Hamisu M.; Henshaw, Chelsea; Salemi, Jason L.; Dongarwar, Deepa; Wudil, Usman J.; Olaleye, Omonike; Godbole, Nupur; Aggarwal, Anjali; Aliyu, Muktar H.
Abstract : Abstract: We sought to determine whether black–white gap in mortality exists among hospitalized HIV-positive patients in the United States (US). We hypothesized that in-hospital mortality (IHM) would be similar between black and white HIV-positive patients due to the nationwide availability of HIV services. Our analysis was restricted to hospitalized HIV-positive patients (15–49 years). We used the National Inpatient Sample (NIS) that covered the period from January 1, 2002 to December 31, 2014. We employed joinpoint regression to construct temporal trends in IHM overall and within subgroups over the study period. We applied multivariable survey logistic regression to generate adjusted odds ratios (OR) and 95% confidence intervals (CI). The total number of HIV-related hospitalizations and IHM decreased over time, with 6914 (3.9%) HIV-related in-hospital deaths in 2002 versus 2070 HIV-related in-hospital deaths (1.9%) in 2014, (relative reduction: 51.2%). HIV-related IHM among blacks declined at a slightly faster rate than in the general population (by 56.8%, from 4.4% to 1.9%). Among whites, the drop was similar to that of the general population (51.2%, from 3.9% to 1.9%). Although IHM rates did not differ between blacks and whites, being black with HIV was independently associated with a 17% elevated odds for IHM (OR = 1.17; 95% CI = 1.11–1.25). In-hospital HIV-related deaths continue to decline among both blacks and whites in the US. Among hospitalized HIV-positive patients black–white disparity still persists, but to a lesser extent than in the general HIV population. Improved access to HIV care is a key to eliminating black–white disparity in HIV-related mortality.